Empowering STEAM Learning Implementation through Investigating Indonesian Teacher Experts’ Views with a Delphi Method - Pasttita Ayu Laksmiwati; Zsolt Lavicza; Adi Nur Cahyono (Universitas Muhammadiyah Surakarta, 2024)
STEAM education has been increasingly adopted by teachers globally in educational settings spanning from elementary school to high school level. However, the challenge is in ensuring that STEAM education adaptation remains relevant to students. In this study, we examined Indonesian teacher experts’ points of view on the pedagogical guidelines for assisting teachers in developing STEAM lessons that are relevant for their students in the Indonesian context. This study employed the Delphi method and involved the participation of eighty teacher experts during a series of three rounds of evaluation processes by analyzing the consensus levels and agreement between rounds. Data were obtained through an online form and subsequently analyzed by descriptive qualitative methods to investigate the quality of several design principles and acquire teacher experts’ recommendations. The findings revealed the consensus between the three rounds on the quality of the design principles. Moreover, the results of this study highlight main dimensions involving technology usage, assessment, contextual problems, integrated STEAM learning, and classroom implementation, which might contribute to advancing knowledge in the field of STEAM education. Therefore, the findings provide recommendations for future research and explorations by focusing on the main dimensions that should be prioritized.